The Relationship Between Serum Delta FSH Level and Ovarian Response in IVF/ICSI Cycles - Hu, Linli; Sun, Bo; Ma, Yujia; Li, Lu; Wang, Fang; Shi, Hao; Sun, Yingpu (Frontiers in Endocrinology, 2020)
Background When ovarian response to FSH stimulation for IVF/ICSI is unsatisfactory, the FSH dose is often adjusted in the treatment cycles, thereby assuming that hormone status and follicular development were insufficient for optimal stimulation. Objectives To evaluate whether serum delta FSH levels between D6 of gonadotrophin use and basal serum FSH or between D6 of gonadotrophin use and D1 of gonadotrophin use predict ovarian response in IVF/ICSI cycles. Method The participants of this retrospective study were chosen from the Reproductive Medicine, The First Affiliated Hospital of Zhengzhou University between August 2015 and December 2017 (n = 3,109), and during the COS, each participant was given a fixed dose of rFSH in the first 6 days. Delta FSH1: The difference of serum FSH between D6 of gonadotrophin use and basal serum FSH. Delta FSH2: The difference of serum FSH between D6 of gonadotrophin use and D1 of gonadotrophin use. Logistic regression was used to analyze the association between delta FSH1 level and delta FSH2 level and ovarian response. Besides, we also use the tertile statistics to divide the groups. Results Part I: Delta FSH1 levels (mean: 1.41 ± 3.46) in normal responders were higher than delta FSH1 levels (mean: 1.07 ± 23.89) in hyper responders (P = 0.0248). The tertile of delta FSH1 is dif ≤ 0, 0 < dif ≤ 2.25 and dif > 2.25. Compared with the hyper responder, the delta FSH1 (0 < dif ≤ 2.25 and dif > 2.25) in the normal responder has a higher ratio and is statistically significant. Part II: Delta FSH2 levels (mean: 4.90 ± 2.84) in normal responders were similar with delta FSH2 levels (mean: 4.74 ± 2.09) in hyper responders (P = 0.103). The tertile of delta FSH1 is dif ≤ 3.91, 3.91 < dif ≤ 5.69 and dif > 5.69. Compared with the hyper responders, the delta FSH2 (3.91 < dif ≤ 5.69 and dif > 5.69) in the normal responders has a higher ratio and is statistically significant. Conclusions There is a weak relationship between ovarian response and serum delta FSH levels.